Transcriptomes of the interaction between Fusarium verticillioides and a Streptomyces strain reveal the fungal defense strategy under the pressure of a potential biocontrol agent. Issue 2 (February 2021) - Strub, C.; Dieye, C.A.T.; Nguyen, P.A.; Constancias, F.; Durand, N.; Guendouz, S.; Pratlong, M.; Fontana, A.; Schorr-Galindo, S.
Abstract: The actinobacteria Streptomyces sp. AV05 appears to be a potential biocontrol agent (BCA) against mycotoxigenic fungi. It was found to significantly inhibit F . verticillioides growth and mycotoxin production during their co-cultivation. F. verticillioides growth was durably affected while the decrease of the toxin production levels was reversible, suggesting different BCA actions. The study of both transcriptomes brought useful information on the microbial interaction. RNA-seq data indicated that the dual interaction modified genetic expression of both microorganisms as 18.5 % of the genes were differentially expressed for the fungus against 3.8 % for the actinobacteria. Fungal differentially expressed genes (DEGs) were equally up and down regulated while bacterial ones were mainly upregulated. We especially focused the analysis of DEGs on fungal defense reaction to bacterial attack. For example, if this potential BCA implements a strategy of antibiosis with the over expression of 'siderophore-interacting protein' linked to the production of bacteriocins, the fungus in a state of stress is able to adapt its metabolism by up-regulation of amidase. It could correspond to the induction of resistance gene clusters and suggest a detoxification process. Moreover fumonisins-related pathway appears underexpressed in the presence of Streptomyces that explain the reduction of fumonisin accumulation observed. Highlights: Fusarium verticillioides is a mycotoxigenic fungus contaminating cereal crop. Streptomyces sp. AV05 is a potential BCA for F . verticillioides . Transcriptome study help to understand antagonistic mechanisms. Fusarium transcriptome is more impacted by confrontation than Streptomyces one.